Does training people to administer take‐home naloxone increase their knowledge? Evidence from Australian programs. (22nd February 2018) - Dietze, Paul M.; Draper, Bridget; Olsen, Anna; Chronister, Karen J.; van Beek, Ingrid; Lintzeris, Nicholas; Dwyer, Robyn; Nelson, Marina; Lenton, Simon
Abstract: Introduction and Aims: Take‐home naloxone (THN) programs have been operating in Australia since 2012 in a variety of settings. We examine whether THN programs were effective in increasing knowledge about opioid overdose and appropriate responses in program participants. Design and Methods: Data were obtained from pre‐ and post‐training questionnaires administered as part of the early evaluations of THN naloxone programs operated in Sydney (n = 67), Melbourne (n = 280), Perth (n = 153) and Canberra (n = 183). Pooled data from comparable items, analysed in the domains specified in previously‐developed evaluation scales, were compared using repeated‐measures analysis of variance and random effects logistic regression. Results pre‐ and post‐training were compared as well as results across sites. Results: High levels of knowledge about overdose risks and signs and appropriate actions to take were observed at baseline and this generally improved over time. No substantial differences were identified across cities. Knowledge also increased with participant age but the improvements over time were similar in each age group. There were small differences by participant gender with knowledge generally higher among females. Discussion and Conclusions: THN programs are effective in improving knowledge related to overdose response. Major improvements in knowledge were limited to overdose recognition and effect of naloxone suggesting that education may best be focused on overdose signs and the use of naloxone among populations accessed through these programs. A focus on younger people also appears warranted. Further work is needed to understand the impact of training and knowledge on actual behaviours around overdose events.